Hormones and Sarcopenia - Morley, John E (Current pharmaceutical design, 2017)
Sarcopenia is defined as the loss of muscle mass associated with a loss of muscle function, e.g., walking speed. A number of consensus definitions exist for sarcopenia with cut-off points being ethnically specific. A rapid screen test (SARC-F) is available and does not require different ethnic cut-off points. Sarcopenia leads to the development of frailty, disability and mortality. The prevalence of sarcopenia varies from 1-29% in community- dwelling and 14 to 33% in long-term care populations. Hormones play a role in the development of muscle mass and in the regulation of muscle strength. Testosterone appears to be the central hormone involved in the development of sarcopenia; it increases both muscle mass and activates satellite cells leading to increased muscle function. Growth hormone deficiency leads to the loss of muscle mass but not muscle strength. Lack of insulin or insulin resistance leads to accelerated development of sarcopenia. Vitamin D deficiency plays a role in the loss of muscle strength. A variety of other hormones appear to play minor roles in age-related alterations in muscle mass and function. At present, the treatment of sarcopenia is resistance exercise, leucine enriched essential amino acids or hydroxymethylbutyrate and vitamin D replacement.